2022
DOI: 10.1038/s41598-022-17113-2
|View full text |Cite|
|
Sign up to set email alerts
|

Sulfated glycosaminoglycans inhibit transglutaminase 2 by stabilizing its closed conformation

Abstract: Transglutaminases (TGs) catalyze the covalent crosslinking of proteins via isopeptide bonds. The most prominent isoform, TG2, is associated with physiological processes such as extracellular matrix (ECM) stabilization and plays a crucial role in the pathogenesis of e.g. fibrotic diseases, cancer and celiac disease. Therefore, TG2 represents a pharmacological target of increasing relevance. The glycosaminoglycans (GAG) heparin (HE) and heparan sulfate (HS) constitute high-affinity interaction partners of TG2 in… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 73 publications
0
4
0
Order By: Relevance
“…More research is required to establish the physiological role of this homodimer and its binding mode to fibrillar FN. Therefore, our results indicate that, like for Syndecan-4 [94] or α5β1 integrins, the FN-binding epitope on TG2 is conformational. Interestingly, studies have identified anti-TG2 autoantibodies that induce a shift in a pool of effector-free TG2 either toward the "closed" or "open" conformation, depending on the epitope on TG2 they bind to [41,106].…”
Section: Discussionmentioning
confidence: 60%
See 2 more Smart Citations
“…More research is required to establish the physiological role of this homodimer and its binding mode to fibrillar FN. Therefore, our results indicate that, like for Syndecan-4 [94] or α5β1 integrins, the FN-binding epitope on TG2 is conformational. Interestingly, studies have identified anti-TG2 autoantibodies that induce a shift in a pool of effector-free TG2 either toward the "closed" or "open" conformation, depending on the epitope on TG2 they bind to [41,106].…”
Section: Discussionmentioning
confidence: 60%
“…8). TG2 is inactive when TG2's N-terminal and C-terminal domains are in spatial proximity due to GDP/GTP binding and/or when TG2 interacts with syndecan-4 [94]. We propose here that TG2 and FN can form additional interactions due to the C-terminal β-barrels making synergistic contacts with FNI 8-9 , while TG2's N-terminal domain interacts with FNI 7 (Fig.…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…MMPs promote new matrix synthesis by fibroblasts, which then secrete TG2 and LOXs to adjust its consistency. A metalloprotease's physiological role is to degrade ECM proteins, thus opposing TG2 crosslinking and stabilization [54,55]. in structural conformation (further influenced by Ca2 + and GTP concentrations).…”
Section: Tumor Type Drug Referencementioning
confidence: 99%